Screening for Mutations in Hereditary Cancer Susceptibility Genes in a Region with High Endogamy in Brazil - Oliveira, Polyanna; Correa, Paula; Acosta, Angelina; Freitas, Juliana; Machado-Lopes, Taísa; Bomfim-Palma, Thais; Ribeiro-dos-Santos, Ândrea; Santos, Sidney; Nascimento, Roberto; Nascimento, Ivana; Abe-Sandes, Kiyoko (Global Medical Genetics, 2023)
Introduction Cancer is a multifactorial disease dependent on the influence of genetic and environmental factors. About 10% of cancers are associated with germline mutations, which predispose to a higher risk of developing cancer. Currently, the use of panels that identify susceptibility and/or association genes cancer has been increasingly used, both in clinical practice and in scientific research.Objective To investigate genetic mutations in patients with a profile for hereditary cancer in individuals from a region of northeast Brazil, where there is a high frequency of endogenous and consanguineous marriages.Methods A set of 17 genes (BRCA1, BRCA2, APC, TP53, PTEN, RET, VHL, RB1, CDKN2, CDH1, CHEK2, MLH1, MSH2, MSH6, MUTYH, XPA, and XPC) associated with cancer and hereditary syndromes were analyzed. Fifteen patients with a hereditary cancer profile were evaluated.Results The pathogenic variant found was c.1187G > A (p.Gly396Asp), rs36053993 in the MUTYH gene in a male patient diagnosed with melanoma at the age of 43 years and a family history for this tumor. This gene encodes an important enzyme related to DNA repair and has been associated with other types of cancer, this is the first report of an association with melanoma, the biological plausibility of this association is given once the MUTYH protein is expressed in the skin tissue and is responsible for repairing damage caused, for example, by sun exposure.Conclusion The results of this study suggest that this mutation may be important for the hereditary predisposition to melanoma, but a broader investigation of this mutation is needed.
Keywords: hereditary cancer; pathogenic variant; multigene panel; endogamy